Relevansi Pemikiran Ibnu 'Arabi Bagi Masyarakat Digital: Sebuah Refleksi Filosofis - Muhtar, Mohamad Khusnial; Hafidz Iman (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2025)
Ibn ‘Arabi is a highly influential philosopher and Sufi within the Islamic civilization. While his thoughts have been extensively studied by scholars, their relevance to the life of digital society has seldom been explored. This research aims to examine the applicability of Ibn ‘Arabi’s thoughts in addressing the challenges and issues faced by digital society, such as social anxiety, dependency on social media validation, and more. The study seeks to offer pathways toward balancing technological advancement with the preservation of spiritual values. Employing a library research method with a philosophical approach, this study aims to produce critical, reflective, and comprehensive insights. Referring to various literature on Ibn 'Arabi and the life of digital society, the findings of this study indicate that Ibn 'Arabi's teachings remain relevant, albeit not in their entirety. The concept of al-Insān al-Kāmil highlights the importance of honesty and inner integrity amid the pressures of social media, encouraging individuals to avoid solely seeking external validation and instead to use digital platforms as a means of spreading goodness and building meaningful connections. Meanwhile, the concept of Waḥdat al-Wujūd teaches that each individual is a manifestation of the One Divine, fostering self-acceptance and gratitude, as well as promoting tolerance for diversity. By understanding and embracing these two concepts, digital society can strive for a balance between technological progress and spiritual awareness, fostering a more meaningful life.